2005
DOI: 10.1093/jpepsy/jsi068
|View full text |Cite
|
Sign up to set email alerts
|

Informant Discrepancy in Perceptions of Sickle Cell Disease Severity

Abstract: Implications for the association between chronic disease and adjustment are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Possible scores range from 0 to 100, with higher scores indicating greater disease severity. Previous research has demonstrated that provider ratings of disease severity via VAS are significantly correlated with objective ratings (i.e., hemoglobin levels and ER visits) in pediatric SCD (Connelly et al, 2005) and was significantly correlated with child report of pain in this study [r(100) ¼ .23, p < 0.05].…”
Section: Disease Severitysupporting
confidence: 56%
“…Possible scores range from 0 to 100, with higher scores indicating greater disease severity. Previous research has demonstrated that provider ratings of disease severity via VAS are significantly correlated with objective ratings (i.e., hemoglobin levels and ER visits) in pediatric SCD (Connelly et al, 2005) and was significantly correlated with child report of pain in this study [r(100) ¼ .23, p < 0.05].…”
Section: Disease Severitysupporting
confidence: 56%
“…Perceptions related to disease severity have also been found to differ between patients and their caregivers, including physicians. Connelly et al showed this discrepancy in their study, in which patients with SCD reported fewer SCD-related symptoms and milder disease severity compared to that reported by their parents and physicians [43]. However, in our study, we did not examine SCD perceptions among different informants.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, in multivariate analyses, married or cohabiting parents reported a higher parent‐proxy discrepancy QoL compared with those who were single, and health care professional‐proxy‐reported discrepancy QoL was higher for children who had not missed any days of school, supporting previous research (Dampier et al ., ). In contrast, previous research has found that disease severity is an important correlate of parent‐proxy‐reported health‐related QoL (Palermo et al ., ; Panepinto et al ., , ), and it might be expected that this would be even more likely to explain health care professional‐proxy reports (Connelly et al ., ). Once again, the reason this was not more important in the present study is likely to be due to the focus on generic QoL.…”
Section: Discussionmentioning
confidence: 97%
“…Days missed from school were also found to be related to child and parent‐proxy reports (Dampier et al ., ). There has been no research into the variables that may be related to health care professional‐proxy reports in the paediatric SCD population, although the degree of disease severity may be a contributing factor (Connelly et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation